Science Communication: It’s More Complex Than Simply Simplifying - Ponce de Leon, Inez Z (Archīum Ateneo, 2020)
In this lecture, Ma'am Inez talks about the value of science communication and translating facts and data into meaningful information. Speaker: NEZ Z. PONCE DE LEON, PhD is an associate professor at the Department of Communication of the Ateneo de Manila University. She graduated with a bachelor of science (cum laude) and a masters degree, both in molecular biology and biotechnology from the University of the Philippines, Diliman. She loved the lab, but she loved communicating science and being in front of audiences. She earned her PhD from Purdue University, and worked on science and risk communication from then on. Inez is also a researcher, novelist, and belly dancer. You can find her online at www.inezpdl.com.